Transcriptomic analysis of ileal adaptations and growth responses in growing hens supplemented with alanyl-glutamine dipeptide - Usman Nazir; Zhenming Fu; Xucheng Zheng; Muhamamd Hammad Zafar; Zhi Yang; Zhiyue Wang; Haiming Yang (Poultry Science)
The growing phase of laying hens is crucial for growth and development due to its direct impact on their productivity during laying phase. During initial growth phase, intestinal tract undergoes rapid development which requires plenty of nutrients to help laying hens grow and mature. This study investigated the effect of Alanyl-Glutamine (Aln-Gln) levels on growth performance, ileal morphology and transcriptomic analysis of growing Hy-line brown hens. A total of 480 day old Hy-line brown chicks having similar body weight (BW) were randomly divided to be fed diets having 0%, 0.1%, 0.2% and 0.3% Aln-Gln for 6-wks (8 replicates/group, 15 birds/replicate). One bird from every pen was slaughtered and morphological parameters of ileum were evaluated. Results taken on day 42 revealed an improved average daily gain (ADG), final body weight (FBW) and feed-to-gain ratio (F/G) in the birds that consumed 0.2% and 0.3% Aln-Gln supplemented diet (P < 0.05). Ileal morphological assays showed that villus height, villus width and villus to crypts ratio (V/C) were significantly increased at 42 days of age in birds fed diets with 0.2% Aln-Gln (P<0.05). The RNA sequencing (RNA-Seq) was executed to identify differentially expressed genes (DEGs) among groups that found 2265 DEGs (1256 up-regulated; 1009 down-regulated) in ileum tissue. According to the Kyoto Encyclopedia of Genes (KEGG) and Genomic Pathway Enrichment Analysis, majority of DEGs indicated change in metabolic pathways. Genes related to growth factors, intestinal morphology and protein metabolism were up-regulated in test groups as compared to control group. In conclusion, addition of Aln-Gln to the diet improved growth performance and ileum development in growing hens; transcriptomic analysis revealed up-regulation of genes related to growth and intestinal morphology.